Pengaruh Pencampuran Kulit Semangka (Citrullus lanatus) dan Mangga Kweni (Mangifera odorata Griff.) terhadap Kualitas Selai Lembaran - Lana Elisabeth Lalujan; Alya Cahyani Putri; Tineke Marlyn Langi; Teltje Koapaha (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to evaluate the effect of mixing watermelon rind (Citrullus lanatus) and kweni mango (Mangifera odorata Griff.) on the color and sensory quality of slice jam while promoting the utilization of fruit-processing by-products. The experiment employed a Completely Randomized Design (CRD) with four treatment ratios of watermelon rind to kweni mango pulp: P1 (20:80), P2 (30:70), P3 (40:60), and P4 (50:50), each replicated three times. Color parameters (L*, a*, b*) were measured using the Color Grab application, and sensory evaluation of color, aroma, taste, and texture was conducted by 25 untrained panelists using a seven-point hedonic scale. Results showed that increasing the proportion of watermelon rind significantly enhanced lightness (L*) and yellowness (b*) while decreasing redness (a*). The sensory test indicated that the P4 formulation achieved the highest overall preference score (5.12), corresponding to a bright golden-yellow color, balanced aroma, and chewy texture. The discussion highlights that the improvement in color and texture is associated with the higher natural pectin content of watermelon rind, which contributes to gel formation and product stability. Moreover, combining kweni mango and watermelon rind demonstrates a viable approach for valorizing agricultural waste into value-added food products. In conclusion, the 50:50 mixture produced the most acceptable slice jam, confirming that watermelon rind can serve as a sustainable, functional ingredient to enhance product quality and support circular-economy practices in tropical fruit processing